DESAIN DAN PENGEMBANGAN PERALATAN REKAYASA OTOMATIS PADA PAPAN TULIS MENGGUNAKAN ARDUINO UNO R3 TERINTEGRASI DENGAN ANDROID: Indonesia - Tri Ferga Prasetyo; Harun Sujadi; Rama Muhamad Azizi (Universitas Majalengka, 2020)
At this time, technological development is something we cannot avoid in this life, because technological progress will be consistent with the advancement of science. The whiteboard is one of the objects whose existence is very important in the teaching and learning process, a classroom as an important tool for writing learning materials. Android is a comprehensive open source platform designed for mobile devices. It is comprehensive because Android provides all the tools and a complete framework for developing applications on a mobile device. The Android system used a database to store important information needed to keep it even when the device is turned off. 3D printing or also known as Additive Layer Manufacturing is the process of making 3-dimensional solid objects or any shape from a digital model. This tool will be created using a technology whiteboard from which consists of hardware, namely Arduino Uno R3 and Expansion Board A4988. The way it works is almost the same as a laser printer with the technique of making objects from a number of layers, each of which is printed on top of each other. To solve this problem, we need a mechanical device that can work automatically and programmed so that it replaces the teacher's task in writing on the whiteboard.